Pomocy!!!Ćw.1. Przekształć sumy algebraiczne i zredukuj wyrazy podobne.
a). (8x-y)+(-2x-4y)-6(-5x-2y)=
b). (-4a-3)-2(-6a+4)+(7a-5)=
c). -(3c-8)+4(2c-6)+(-8a-3)=
d). 1-(-4x-5y+2)-3(6x-8y-3)=
e). -4+2(-3x+5)-8(4x-6)=
f). -(2x+4y-6)+4(-x-y+2)=
g). -(3x+2a)-3(x+4a)+(-6a+5)=
h). 7x-(-2x+4)-4(3x-6)-15=
i). (3a+4c-8)-2(a-2c-6)+(-8a-3c-7)=
j). -(-2a+8)-3(-6a+3)+(18a-9)=
Ćw.2.Zredukuj wyrazy podobne.
a). -4x-7-3x+7= b). x-2xy+1/2x-1/3xy=
c). -x kwadrat+y kwadr.-2x kwadr.-2y kwadr.=
d). -x kwadr.+2x-3x+x kwadr.= e). 4x+4-7x-1/2=
f). -2ab+12a-4ab-16a=
Cw.3. Wykonaj działania.
a). a+(a-b)= b). 2x-(x+4)= c). 7-(-x+6)=
d). -(x+4)+(x-5)= e). 1-((t+p)-(t-2)= f). -(-y+2)+(-2y-4)=

2

Odpowiedzi

2010-03-01T17:46:02+01:00
Zad 1
a).(8x-y)+(-2x-4y)-6(-5x-2y)=8x-y-2x+4y+30x+12y=36x+15y
b). (-4a-3)-2(-6a+4)+(7a-5)=-4a-3+12a-8+7a-5=15a-16
c). -(3c-8)+4(2c-6)+(-8a-3)=-3c+8+8c-24-8c-3=-3c-19
d). 1-(-4x-5y+2)-3(6x-8y-3)=1+4x+5y-2-18x+24y+9=-14x+29y+8
e). -4+2(-3x+5)-8(4x-6)=-4-6x+10-32x+48=-26x+54
f). -(2x+4y-6)+4(-x-y+2)=-2x-4y+6-4x-4y+8=-6x+14
g). -(3x+2a)-3(x+4a)+(-6a+5)=-3x-2a-3x-12a-6a+5=-6x-20a+5
h). 7x-(-2x+4)-4(3x-6)-15=7x+4x-4-12x+24-15=-x+5
i). (3a+4c-8)-2(a-2c-6)+(-8a-3c-7)=3a+4c-8-2a+4c+12-8a-3c-7=-7a+5c-3
j). -(-2a+8)-3(-6a+3)+(18a-9)=2a-8+18a-9+18a-9=38a-26
zad 2
a). -4x-7-3x+7= -7x
b). x-2xy+1/2x-1/3xy=1 1/2x - 2 1/3xy
c). -x kwadrat+y kwadr.-2x kwadr.-2y kwadr.=-x²+y²-2x²-2y²=-3x²-y²
d). -x kwadr.+2x-3x+x kwadr.= -x²+2x-3x+x²=2x-3x
e). 4x+4-7x-1/2=-3x+3 1/2
f). -2ab+12a-4ab-16a=-6ab-4a

zad 3
a). a+(a-b)= a+a-b=2a-b
b). 2x-(x+4)= 2x-x-4=x-4
c). 7-(-x+6)=7+x-6=x+13
d). -(x+4)+(x-5)= -x-4+x-5=-9
e). 1-((t+p)-(t-2)= 1-(t+p)-t+2)= 1-t-p+p-t-2=-1-2t
f). -(-y+2)+(-2y-4)= y-2-2y-4=-y-6
2010-03-01T17:49:53+01:00
Ćw.1.
a). (8x-y)+(-2x-4y)-6(-5x-2y)=8x-y-2x-4y+30x+12y=36x+7y
b). (-4a-3)-2(-6a+4)+(7a-5)=-4a-3+12a-8+7a-5=22a-16
c). -(3c-8)+4(2c-6)+(-8a-3)=3c+8+8c-24-8a-3=-8a+11c-19
d). 1-(-4x-5y+2)-3(6x-8y-3)=1+4x+5y-2-18x+24y+9=-14x+29y+8
e). -4+2(-3x+5)-8(4x-6)=-4-6x+10-32x+48=-38x+54
f). -(2x+4y-6)+4(-x-y+2)=2x-4y+6-4x-4y+6=-2x-8y+12
g). -(3x+2a)-3(x+4a)+(-6a+5)=3x-2a-3x-12a-6a+5=-20a+5
h). 7x-(-2x+4)-4(3x-6)-15=7x+2x-4-12x+24-15=-3x+6
i). (3a+4c-8)-2(a-2c-6)+(-8a-3c-7)=3a+4c-8-2a+4c+12-8a-3c-7=-8a+6c-3
j). -(-2a+8)-3(-6a+3)+(18a-9)=2a-8+18a-9+18a-9=38a-26
Ćw.2.
a). -4x-7-3x+7= -7x
c). -x kwadrat+y kwadr.-2x kwadr.-2y kwadr.=-3x²-y²
d). -x kwadr.+2x-3x+x kwadr=-x
f). -2ab+12a-4ab-16a=-4a-6ab
Cw.3.
a). a+(a-b)=a+a-b=2a-b
b). 2x-(x+4)=2x-x-4=x-4
c). 7-(-x+6)=7+x-6=x+1
d). -(x+4)+(x-5)=-x-4+x-5=-9
f). -(-y+2)+(-2y-4)=y-2-2y-4=-y-6